2011
DOI: 10.3758/s13414-011-0259-7
|View full text |Cite|
|
Sign up to set email alerts
|

Sink positive: Linguistic experience with th substitutions influences nonnative word recognition

Abstract: We used eyetracking, perceptual discrimination, and production tasks to examine the influences of perceptual similarity and linguistic experience on word recognition in nonnative (L2) speech. Eye movements to printed words were tracked while German and Dutch learners of English heard words containing one of three pronunciation variants (/t/, /s/, or /f/) of the interdental fricative /θ/. Irrespective of whether the speaker was Dutch or German, looking preferences for target words with /θ/ matched the preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 64 publications
4
47
1
Order By: Relevance
“…Thus, no overt, decision-based response was required. This type of design has previously been used in a similar study investigating accented speech (Hanulíková & Weber, 2012). In the current study, the main manipulation was the degree of accentedness of the auditory items.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, no overt, decision-based response was required. This type of design has previously been used in a similar study investigating accented speech (Hanulíková & Weber, 2012). In the current study, the main manipulation was the degree of accentedness of the auditory items.…”
Section: Methodsmentioning
confidence: 97%
“…As the auditory stimulus unfolds and more information becomes available to the listener, the set of candidates decreases allowing listeners to settle on the intended target. However, Hanulíková and Weber (2012) have shown that this paradigm can be used to investigate the effect of accent on the time-course of word recognition as measured by looks to the target over time. In this same vein, Experiment 2 utilized the Visual World Paradigm to examine the influence of gradient foreign accentedness on the time-course of spoken word recognition.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations